PREVENTION OF INJURIES IN THE GAME OF HANDBALL LOCALED AT THE LEVEL OF THE UPPER LIMBS - Popa Roxana-Nicoleta; Ene-Voiculescu Virgil; Seciu Alex-Paul (Sport şi Societate)
Handball is a sports game that allows direct contact with opposing players, it is a sport whose basic motor quality is strength, and nowadays the practice of performance handball implies a great willingness to act as a consequence of aspects such as the fact that the actions are not standardized but are very dynamic and determine the athlete to develop a capacity for anticipation of both the teammate, and of the opponent. Trauma to the shoulder joint in high-performance handball players is based on mistakes in practicing this sport, direct blows applied to soft tissues, intentional irregular practice, holding, very brutal attacks, pushing, intentional hitting with the purpose of intimidating the opponent and hugging. The neuro-myo-arthro-kineticapparatus is highly demanded by the theme of the handball sports game, the practice of playing in strength and speed determines the body to adapt to the specifics of effort, namely to the complex and dynamic situations imposed by performance handball. In this sense, the principles that were the basis of the experiment have both theoretical and practical roots, starting from the idea that any injury to the body of the performance handballer, especially that trauma that forces the athlete to rest, has repercussions both on his quality as a player and on the entire team. For an active life, we must take into account certain aspects such as body health, its preservation, improvement or regain, the functional capacity of the body, the harmonious body appearance and the balanced nutritional status, these can only be acquired through the interdisciplinarity formed by sport, kinesiotherapy and medicine. Taking into account the fact that the game of handball is a sport for which the upper limb is the number 1 game instrument, we must specify that for the performance handballer, the upper limb represents a trait of him as an athlete, an organ of manifestation of professionalism and sports personality by the fact that during the handball game he uses his entire arm for a determined action by putting it in a precise and beneficial position, with maximum efficiency.